The pot book : a complete guide to cannabis : its role in medicine, politics, science, and culture - Holland, Julie, 1965- (Park Street Press, 2010)
"Leading experts on the science, history, politics, medicine, and potential of America's most popular recreational drug"--Provided by publisher.